Fluorescence and photostability studies of anthracene-9-carboxylic acid in different media - M. S. A. Abdel-Mottaleb; H. R. Galal; A. F. M. Dessouky; M. El-Naggar; D. Mekkawi; S. S. Ali; G. M. Attya (International Journal of Photoenergy)
Electronic absorption and fluorescence spectra of anthracene-9-carboxylic acid (ANCA) were studied in different homogeneous solvents, binary protic/aprotic solvent mixtures and in heterogeneous solutions of the cationic cetyltrimethyl ammonium bromide (CTAB) micelle. Different chemical species of ANCA were identified spectroscopically in different media. The results are discussed on the basis of a mechanism that involves two equilibria: acid-base equilibrium and monomer-dimer equilibrium. These equilibria were found to be very sensitive to the nature of the medium and the concentration of ANCA.